Levels of Research in Genetics and the Concept of Gene - Rubikas, Jonas (Problemos, 1995)
The methodology of genetics is discussed in the paper. Five levels of research are pointed out. Every level of research is characterized by the object of research and by the criterion of evaluation. The levels and their main concepts are: I. Organism-feature. This is the level of the systematics of living organisms. II. Cell-feature. A cell – gamete – contains discrete particles, which determine all inherited features of an organism. III. Chromosome-feature. The particles are chromosomes and contain aligned genes – determinants of the inherited features. IV. DNA-feature. A chromosome contains a chemical compound – deoxyribonucleic acid (DNA), which is genetic material: a definite fragment of DNA can transfer a feature from one organism to another. V. DNA (RNA) nucleotide sequence-function. The main idea of this level is that definite functions are coded by certain nucleotide sequences. The gene definition of the fifth, contemporary, level is that the gene is the structure which has a function of information. There must be an optimal correspondence between the question, method, and answer in a scientific work.